Hemato-Biochemical Studies in Theileriosis Infected Gir Cows and Jaffrabadi Buffaloes - Brahmbhat, Nilima N.; Dodia, Vaibhavsinh D.; Vasava, Amrita A.; Kumar, Binod; Thakre, Bhupendrakumar J.; Bilwa, Avinash. K. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
This study was conducted to assess the hemato-biochemical alterations in theileriosis infected Gir cows and Jaffrabadi buffaloes from the southwestern region of Gujarat, India. The prevalence of theileriosis in indigenous bovines was studied by screening 518 blood samples of clinically suspected animals during one year period. Among the screened samples, 85 were found to be Theileria spp. positive microscopically. Overall, significantly higher (p 1 year compared to younger ones 0.05) in both cattle and buffaloes. Hematological analysis revealed significant (p
Keywords: Gir cattle; Hematology; Jaffrabadi buffaloes, Prevalence, Seasonal influence; Serum biochemistry; Theileriosis.